Certainty of evidence, why? - João Pedro Lima; Xiajing Chu; Gordon H Guyatt; Wimonchat Tangamornsuksan (Jornal Brasileiro de Pneumologia, 2023)
ABSTRACT Optimal clinical decision-making requires understanding of evidence regarding benefits, harms, and burdens of alternative management options. Rigorously conducted systematic reviews and meta-analyses offer accurate summaries of the evidence. However, such summaries may review only low-certainty evidence, in the process highlighting that no single decision is likely to be best for all patients. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach offers a systematic and transparent method for rating certainty of evidence in systematic reviews. In this paper, we will address the importance of assessing the certainty associated with bodies of evidence; explain how the GRADE system rates the certainty of evidence from systematic reviews; and present the GRADE evidence to decision framework for moving from evidence to strong or weak recommendations in clinical practice guidelines.